Telling stories, performing operations as a design method - Kristanti Dewi Paramita (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
Exploration of stories in architectural discourse has yet to generate a structured discussion in the methods of its operations as part of a design endeavour. This issue of ARSNET presents a collection of articles that demonstrates a variety of everyday stories emerging from the experience of space and objects, and outlines the methodologies of their corresponding spatial operations. Through the stories of occupying, manoeuvring, navigating, dispersing, and sensing, this issue highlights various methods of spatial operations. With operations ranging from tracing as a way of revealing space, reduction as manoeuvring strategy, connecting the virtual and the real as a way of finding new meaning and use of space, and creating a spatial atmosphere based on trajectories of senses; the issue expands the discussion of stories-driven architectural design methods.